2019
DOI: 10.1126/scitranslmed.aax4204
|View full text |Cite
|
Sign up to set email alerts
|

Variable gene expression and parasite load predict treatment outcome in cutaneous leishmaniasis

Abstract: Patients infected with Leishmania braziliensis develop chronic lesions that often fail to respond to treatment with antiparasite drugs. To determine whether genes whose expression is highly variable in lesions between patients might influence disease outcome, we obtained biopsies of lesions from patients before treatment with pentavalent antimony and performed transcriptomic profiling on these clinical samples. We identified genes that were highly variably expressed between patients, and the variable expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
126
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(143 citation statements)
references
References 55 publications
(93 reference statements)
12
126
1
Order By: Relevance
“…Next, we sought to locally identify the inflammatory profile in CL and CL + DM lesions, since the production of lipid mediators and the cellular infiltrate could define susceptibility to Leishmania spp . [ 20 , 31 ]. Representative images of CL lesions ( Figure 4 (A)) show the cellular infiltrate of CL subjects (left) and CL + DM individuals (right).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we sought to locally identify the inflammatory profile in CL and CL + DM lesions, since the production of lipid mediators and the cellular infiltrate could define susceptibility to Leishmania spp . [ 20 , 31 ]. Representative images of CL lesions ( Figure 4 (A)) show the cellular infiltrate of CL subjects (left) and CL + DM individuals (right).…”
Section: Resultsmentioning
confidence: 99%
“…Further, GSEA pathways involved in "induction of B-cell receptors" and "NF-κB activation in B cells" involved in B-cell development and activation 43 were positively enriched in the UCL group. Previous human studies have suggested that B-cell activation can lead to the exacerbation of CL disease 19,44 . The involvement of B-cell responses to Leishmania appears to be complex, and whether they participate in parasite persistence or killing remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed genes (DEGs) were examined by edgeR package 44 . The parasite burden from RNAseq data was measured by normalizing the library size 45 . The gene expression values used were the TMM-normalized log CPM values.…”
Section: Methodsmentioning
confidence: 99%